Fruit as diagnostic characteristic to recognize Brazilian species of Zornia (Leguminosae, Papilionoideae) - Fortuna-Perez, Ana Paula [UNESP]; Lewis, Gwilym Peter; Queiroz, Rubens T.; Santos-Silva, Juliana; Tozzi, Ana Maria Goulart de Azevedo; Rodrigues, Karina Fidanza (Magnolia Press, 2015)
Articles of the lomentaceous fruits encountered in the thirty-six species of brazilian Zornia species are described, illustrated and compared using scanning electron microscopy and stereomicroscopy. Macro-and micro-morphological characters of the fruit articles provide excellent diagnostic taxonomic characters (including fruit shape, fruit article surface, presence/absence of glands, presence/absence of bristles, and presence/absence of hairs) to distinguish among the brazilian taxa. results generally support the species recognised for brazil although the micro-morphological characters have limited taxonomic value within some species complexes, in which taxa can be better differentiated using other morphological characteristics. the results of macro-morphological analyses show that the morphology of fruit articles is related to the geographical distribution pattern of each species and is a good source of morphological character to distinguish the species of Zornia. we present here an inedit identification key, based on the loment morphology, to distinguish the brazilian species of Zornia.
Keywords: Dalbergieae; Fabaceae; Faboideae; Lomentum; Morphology; Scanning Electron Microscopy (SEM)